IMPLEMENTASI METODE TALAQQI DALAM MATA PELAJARAN AL-QUR’AN SISWA KELAS 2B KMI DI PMDG KAMPUS 7 KALIANDA - Hadi Syarifudin Ramadhani; Ahmad Luviadi; M. Rizkal Fajri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyse the application of the talaqqi method in learning the Qur'an in class 2B Kulliyatul Mu'allimin Al-Islamiyah (KMI) students at Pondok Modern Darussalam Gontor. Using a qualitative approach with a case study design, data were obtained through in-depth interviews with various informants who were directly involved in the learning process, coinciding with the implementation of the at-tarbiyah al-'amaliyah exam for KMI final students. The informants consisted of one examining teacher, two Grade 6 students as the supervisory team, one Qur'an teacher, and three Grade 2B students. The selection of informants was based on their experience, activeness, and involvement in Qur'anic learning. Data analysis was conducted using a phenomenological approach, which emphasises the subjective experience and understanding of the informants. The results showed that the teacher's readiness before teaching as well as the ability to teach according to procedures greatly influenced the effectiveness of learning and student engagement. Although the talaqqi method proved effective in shaping the quality of Qur'an recitation, some challenges remain, such as time constraints and differences in students' abilities. This study recommends improving teaching strategies, including more careful planning and regular evaluation, to overcome obstacles and optimise learning outcomes both inside and outside the classroom.